2008
DOI: 10.1088/0953-8984/20/40/404207
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic response of block copolymer wormlike micelles to shear flow

Abstract: The linear and nonlinear dynamic response to an oscillatory shear flow of giant wormlike micelles consisting of Pb-Peo block copolymers is studied by means of Fourier transform rheology. Experiments are performed in the vicinity of the isotropic-nematic phase transition concentration, where the location of isotropic-nematic phase transition lines is determined independently. Strong shear-thinning behaviour is observed due to critical slowing down of orientational diffusion as a result of the vicinity of the is… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
27
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 22 publications
2
27
0
Order By: Relevance
“…1(b)i) is identified that is followed sequentially by plastic deformation, indicating that the material is forced to yield. This behavior is typical for a yielding fluid and has been observed for systems ranging from hard [25] and soft spheres [26] to wormlike micelles [17,18,27] and polymers [28]. Furthermore, it is clear from the similarity of the slopes of the elastic portions of the Lissajous curves in Fig.…”
supporting
confidence: 67%
See 2 more Smart Citations
“…1(b)i) is identified that is followed sequentially by plastic deformation, indicating that the material is forced to yield. This behavior is typical for a yielding fluid and has been observed for systems ranging from hard [25] and soft spheres [26] to wormlike micelles [17,18,27] and polymers [28]. Furthermore, it is clear from the similarity of the slopes of the elastic portions of the Lissajous curves in Fig.…”
supporting
confidence: 67%
“…The nematic phase of kaolite submitted to LAOS displays a strain hardening and a maximum strain after which the system seems to soften [14,15]. The mechanism, however, is unclear.The combination of LAOS and an appropriate in situ scattering technique is a useful tool to study structural responses underlying complex flow behavior [16][17][18]. The advantage of LAOS is that material states are probed, which are inaccessible to standard rheological methodologies.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…We can assume that the micellar gels prepared from cylindrical or branched rod-like micelles give rise to higher structural arrangement, where elongated polystyrene cores act as robust constitutive elements of these systems. 33 However, axial extension of this structural component is relatively restricted because of the glassy elongated micellar core. Considering a kinetically frozen micellar core at such low toluene content, we can assume that the PtBA coronal chains are the most subjected under stress.…”
Section: Resultsmentioning
confidence: 99%
“…We then move to birefringence experiments that reveal local nematic ordering in vibrated suspensions that are initially isotropic at rest. These measurements are successfully compared to numerical simulations based on a Smoluchowski approach 19,20 . Our results point to the existence of an out-of-equilibrium phase transition induced by a hydrodynamic instability in suspensions of rodlike colloids.…”
Section: Introductionmentioning
confidence: 99%